4. KONSISTENSI VISI KEPALA DAERAH DENGAN APBD DALAM PENINGKATAN KESEJAHTERAAN RAKYAT DI JAWA TENGAH - Warsito Warsito (JIIP: Jurnal Ilmiah Ilmu Pemerintahan, 2015)
Regional head vision is the ideals to be achieved in five years in the form of the local medium term development plan (RPJMD). The vision must be able to be implemented in the local revenue and expenditure budget (APBD) either in the programs or activities with the support of sufficient funding. This research aims to understand the consistency of the vision and the budget through qualitative method. The results showed that the vision has been consistent with APBD. However, the consistency was not followed by appropriate budget allocations. The height budget allocation for personnel expenditures and bureaucratic routines become one of the causes.